Quality of life in patients with vitiligo: a cross-sectional study based on Vitiligo Quality of Life index (VitiQoL) - Hedayat, Kosar (Health Qual Life Outcomes, 2016)
BACKGROUND: Vitiligo is a multi-factorial pigmentary skin disorder. Recently, the importance of emotional and psychological issues is proposed in incidence, progression, relapse and remission of vitiligo. There are limited studies conducted in developing countries, which assess life quality of patients with vitiligo. The aim of this study was the application and evaluation of a disease-specific quality of life index in Iranian patients, for the first time. METHODS: This cross-sectional biphasic study was conducted on 25 patients as a pilot and another 173 patients as the main study group, in Razi Hospital, Tehran, Iran, 2013–2014. Persian version of Vitiligo Quality of Life index (VitiQoL) was developed with backward-forward method. Based on the pilot study, the validity and reliability were assessed. The Vitiligo Area and Score Index (VASI), VitiQoL, and their relationship, demographic and clinical characteristic of patients were measured. RESULTS: The Mean and standard deviation of the VitiQoL score was 30.5 ± 14.5 (range 0–60 in Persian version). There was a significant relationship between VASI score and VitiQoL (p = 0.015, r = 0.187). Confirmatory factor analysis revealed three important factors within VitiQoL: participation limitation, stigma, and behavior. In subscale analysis based on behavior factor, female patients had poorer quality of life (p = 0.02). Concomitant psychiatric problems, e.g. anxiety and depression, were not associated with QOL; however, they were near to being meaningful (p = 0.06, r = 0.14). CONCLUSION: VitiQoL is a valid index in estimating life quality of vitiligo patients and has proper relation to disease severity. Focusing on patient’s life quality is an important entity in the management of vitiligo patients; relevant supportive group-based consultations and therapies are also important arms when approaching vitiligo. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12955-016-0490-y) contains supplementary material, which is available to authorized users.